2013
DOI: 10.3390/jcm2020013
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Verrucae Pedis Using Falknor’s Needling Method: A Review of 46 Cases

Abstract: Human Papilloma Virus (HPV) related verrucae pedis persist, seemingly evading host immune surveillance, yet sometimes disappear with inflammation. The absence, or reduction, of a cellular immune response may explain why verrucae treatments are not uniformly successful and treatment can be difficult even in immune-competent individuals. Little investigation has been undertaken into the potential benefit and efficacy of needling verrucae, a treatment modality causing HPV infected keratinocyte destruction in addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…The clearance rate for the needling group was 65% (11 of 17), which is approximately 4·5 times greater than our corresponding rate of 14% (four of 28). Similarly, Longhurst and Bristow reported a 69% (31 of 45) resolution of verrucae in a retrospective case series analysis. However, our results are similar to the EVerT trial, which reported a 14% cure rate for both salicylic acid treatment and cryotherapy …”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…The clearance rate for the needling group was 65% (11 of 17), which is approximately 4·5 times greater than our corresponding rate of 14% (four of 28). Similarly, Longhurst and Bristow reported a 69% (31 of 45) resolution of verrucae in a retrospective case series analysis. However, our results are similar to the EVerT trial, which reported a 14% cure rate for both salicylic acid treatment and cryotherapy …”
Section: Discussionmentioning
confidence: 80%
“…Our study followed the same treatment protocols as Longhurst and Cunningham, with the exception that participants in our needling group were given one treatment. Longhurst and Bristow reported a high resolution rate (38 of 45) after one needling treatment. Cunningham et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the face of it this latest trial may not appear to be much of step forward; indeed it is not, but there are some lessons to be learned: The bright hope of needling as an effective treatment for plantar warts appears to have been somewhat dashed by this new trial. Two previous studies, a case series and a randomized trial, showed apparently promising results from this type of treatment with clearance rates of 60–70%. Altogether then, the needling story is beginning to look a bit like the duct tape story where a wave of enthusiasm followed the quirky Focht et al .…”
mentioning
confidence: 87%